174k views
2 votes
X-6 =-1/6y^2 and 2x+y=6. Solve the linear quadratic equation

1 Answer

2 votes

Answer:


(4.5,-3)\textrm{ and }(0,6)

Explanation:

Given:


x-6=-(1)/(6)y^(2)


2x+y=6

Express
x in terms of
y and then plug in first equation to solve for
y.


2x+y=6\\2x=6-y\\x=(6-y)/(2)

Now,


x-6=-(1)/(6)y^(2)\\(6-y)/(2)-6=-(1)/(6)y^(2)\\(1)/(6)y^(2)+(6-y)/(2)-6=0.

Multiply 6 on both sides.


6((1)/(6)y^(2)+(6-y)/(2)-6)=6(0)\\y^(2)+3(6-y)-36=0\\y^(2)+18-3y-36=0\\y^(2)-3y-18=0\\(y-6)(y+3)=0\\y=6\textrm{ or }y=-3

Now, for
y=-3,x=(6-(-3))/(2)=(6+3)/(2)=(9)/(2)=4.5

For,
y=6, x=(6-6)/(2)=0.

Therefore, the solutions for the system of equations are
(4.5,-3)\textrm{ and }(0,6)

User Yifu Yan
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.